Motivation, Discipline, and Ethics : Determinants of Elementary School Students' IPAS Learning Attitude - Nashiruddin Latif; Muh. Yunus; Elpisah Elpisah; Suarlin Suarlin (International Journal of Social Welfare and Family Law, 2025)
This study investigates the influence of learning motivation, student discipline, and ethics on sixth-grade students’ learning attitudes in IPAS at UPT SPF SD Negeri Ujung Tanah 1 Makassar. Employing a quantitative approach with a saturated sample of 65 students, data were collected using questionnaires and analyzed through multiple linear regression with SPSS 26. The results demonstrate that motivation, discipline, and ethics each positively and significantly affect students’ learning attitudes. Simultaneously, these variables jointly influence learning attitudes significantly. Among them, student ethics was identified as the most dominant predictor. These findings suggest that fostering ethical behavior and enhancing motivation and discipline is critical in shaping positive learning attitudes among elementary students in the context of IPAS.